Efficacy of sevoflurane for maintenance of propofol anaesthesia in dogs - Raghavan K.S (Department of Veterinary Surgery and Radiology,College of Veterinary and Animal Sciences, 2010)
The present study was aimed to determine the efficacy of sevoflurane for maintaining propofol anaesthesia in dogs. The study was conducted in 12 dogs of either sex, different age groups, breed and body weight brought for various surgical procedures at Veterinary hospitals Mannuthy and Kokkalai, College of Veterinary and Animal Sciences, Mannuthy. Six healthy animals for surgical procedures with American Society of Anaesthesiologists (ASA) status level I and II for anaesthesia were included in Group I and those six animals for surgical procedures in compromised condition with ASA status level III and IV were included in Group II. Glycopyrrolate at the rate of 0.011 mg/kg body weight, followed by xylazine at the rate of 1 mg/kg body weight at 15 minutes interval were administered intramuscularly for premedication in both the groups. Fifteen minutes later, propofol at the rate of 4 mg per kg body weight was administered by intravenous bolus injection for induction of anaesthesia. Anaesthesia was maintained with sevoflurane (2.5 to 6.0 %) in pure oxygen by Bain’s circuit system utilising sevoflurane vaporiser. The salient clinical signs observed following premedication in both the groups were winking of eyes, lowering of head, scanty salivation, incoordination of gait, ataxia and sitting on haunches followed by sternal recumbency with head down posture. The time for induction of anaesthesia was 1.17 ± 0.17 and 0.92 ± 0.05 minutes in Group I and in Group II animals respectively. Endotracheal intubation was possible in all the dogs. The maintenance quality was good to excellent in animals of both the groups. All surgical procedures were performed in medium plane of surgical anaesthesia. Sevoflurane maintenance provided a good controllable depth of anaesthesia with good to excellent degree of muscle relaxation. The duration of anaesthesia was 56.67 ± 4.09 and 72.50 ± 4.47 minutes in Group I and II animals respectively. The depth of anaesthesia was satisfactory in all the dogs. The recovery time was 18.50 ± 3.19 minutes in Group I and 29.00 ± 1.75 minutes in Group II animals Recovery quality was excellent in all the dogs of both the groups. Vocalisation, regurgitation and sneezing were the undesirable side effects observed during post anaesthetic period. The rectal temperature and respiratory rate recorded a decrease while pulse rate and peripheral haemoglobin oxygen saturation level recorded an increase with sevoflurane maintained anaesthesia in both the groups.The electrocardiographic changes were only transient and got corrected spontaneously during recovery period in both the groups.The colour of mucous membrane was pale roseate in all animals of Group I. The two animals of Group II had pale and four had congested mucus membranes. In general other than an increase in erythrocyte sedimentation rate, capillary refill time and clotting time all haematological parameters like volume of packed red cells and total leukocyte count observed a decrease during sevoflurane maintained anaesthesia. There had non significant fluctuations with in the physiological limits in the lymphocyte, neutrophil, eosinophil, monocyte counts and serum total protein levels on account of anaesthesia, except in Group II animals. There were only non significant fluctuations from the preanaesthetic values in the blood urea nitrogen, creatinine, aspartate aminotransferase and alanine aminotransferase levels in both the groups. All the animals had smooth and uneventful recovery from anaesthesia and surgery.